Return-to-play performance after injury in National Basketball Association League basketball players - Elif Cengizel; Alperen Altıntaş (Central European Journal of Sport Sciences and Medicine, 2025)
The aim of this retrospective study was to compare the return-to-play performance after injury in National Basketball Association (NBA) players according to their surgery status, skin color, player positions, injury location, type, and duration. Fifty-four NBA players who sustained an injury between 2018 and 2022 seasons were identified and only five match before and after the injury were examined to determine the acute effect of the injury. A significant decrease in minutes per game (MPG, pre-injury: 27.4±8.4min, post-injury: 25.5±6.9min, p=.019), field goal points (FGP, pre-injury: 5.4±2.9, post-injury: 2.4±0.3, p=.008), and field goal attempted (FGA, pre-injury: 11.6±5.9, post-injury: 5.2±0.7, “large” ES: 1.52, p=.004) in NBA players after the injury. 70.4% of the injured athletes underwent surgery, 72.2% were black skin color players, the most injured player position was guards (37%), the most injured area was the lower extremity (40.7%), 59.3% were broken, and most of them had an injury duration between 7-30 days (31.5%). The NBA players who returned to play after injury showed a significant decrease in MPG, FGP, FGA. The findings of this research provide important indicators for sports medicine physicians, coaches, and practitioners and can be a guide to understanding how return-to-play performance is affected by injury factors.